2015
DOI: 10.18203/2394-6040.ijcmph20150942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on bone mineral density

Abstract: Background: Body mass index (BMI) is a good indicator for measurement of bone mineral density (BMD) which measures the density of minerals present in the bones using a special scan. BMD can be used to assess the strength of bones. Osteoporosis is a natural phenomenon of wear and tear. Obesity is an independent risk factor for low BMD. Dual-energy X-ray absorptiometry (DEXA) is the most accurate way to measure BMD. DEXA is a gold standard technique for diagnosing osteoporosis. Hence the current study was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In line with this study, exercise has been previous demonstrated to be associated with higher BMD [ 37 40 ]. It would be better to have assessed the relation between weight-bearing exercise and calcaneal OSI in detail.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with this study, exercise has been previous demonstrated to be associated with higher BMD [ 37 40 ]. It would be better to have assessed the relation between weight-bearing exercise and calcaneal OSI in detail.…”
Section: Discussionsupporting
confidence: 90%
“…Further investigation taking the exercise type into consideration is recommended. Increased BMD was also associated with obesity and overweight [ 28 , 40 , 41 ]. The association of obesity/overweight with BMD is probably due to the conversion of androgen to estrogen which increases bone mass [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it is important to remember that not all types of fat are beneficial for bone mass. Low BMI individuals lose more bone compared to those with higher BMI individuals [23]. Similarly, the smokers had three times more probability of having osteoporosis than nonsmokers which is supported by different studies [24, 25].…”
Section: Discussionmentioning
confidence: 82%
“…Higher mechanical loading on the skeleton, in addition to the capability of fat cells, to convert androgens to 17β-estradiol are some of the reasons behind the decreased risk of osteoporosis in overweight and obese individuals. 45 - 47 …”
Section: Discussionmentioning
confidence: 99%